Financial Universe : Planning Your Investments Using Astrological Forecasting. - Skinner, Christeen (Sussex Academic Press, 2009)
Written by one of the world's foremost financial astrologers, this work highlights the periods to maximize investment returns while minimizing portfolio losses through exposure to geopolitical events and circumstances and financial market hotspots. This important new and revised text maps out potential responses by international stock markets to world events that are predicted between now and the year 2020. With no previous understanding astrological terminology needed, The Financial Universe makes deconstructing the complex relationships.